THE ROLE OF RELIGIOUS MODERATION IN THE ISLAMIC BOARDING SCHOOL CURRICULUM AS THE IMPLEMENTATION OF RAHMATAN LIL'ALAMIN ISLAMIC TEACHINGS A STUDY OF TOLERANT CHARACTER DEVELOPMENT IN THE SYAICHONA CHOLIL ISLAMIC BOARDING SCHOOL, KUTAI TIMUR - Syah, Susilo Romadon; Zamroni, Zamroni; Tamam, Badrut (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study explores the role of religious moderation in the curriculum of Syaichona Cholil Islamic Boarding School in East Kutai as an implementation of the Islamic teachings of rahmatan lil-‘alamin (mercy for all worlds). One of the key approaches emphasized at this pesantren is religious moderation, which aligns with the principle of fostering peace and tolerance. The research focuses on how religious moderation is integrated into the pesantren’s curriculum and its impact on character development, specifically in nurturing tolerance among students. Using a descriptive qualitative method, this study examines the pesantren's efforts to enhance religious moderation, embody the teachings of rahmatan lil-‘alamin, and promote a tolerant attitude within its educational framework. The findings highlight the significant role of pesantren in shaping students’ values and behaviors through a balanced approach to religious education, fostering a more inclusive and harmonious society.